Pendampingan Pada Komunitas Anak Disabilitas di Kota Pekanbaru Melalui Pemahaman Hak-Hak Aksessibilitas - Hengki Firmanda; Emilda Firdaus; Nabella Puspa Rani (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2021)
The first fact is still found by parents who have not paid special attention to children with disabilities, resulting in violations of the rights of children with disabilities. The second fact is that the legal instruments are still weak and the regulations have not been fully implemented. These facts are an inhibiting factor in the development of children with disabilities. The purpose of this activity is so that children with disabilities know what their rights are, so that children with disabilities still feel respected by their presence. The output of this activity is the fulfillment of accessibility rights for children with disabilities in their growth and development in the social environment. The result of this activity is that children with disabilities know their rights, so that discrimination against them is not allowed. Children with disabilities also know that they have special rights guaranteed by laws and regulations.